Organ Transportation Thermoelectric Cooling System Design and Application - Yavuz Selim TASPINAR; Prof. Dr. Hakan IŞIK (International Journal of Applied Methods in Electronics and Computers, 2021)
Thermoelectric modules are used in medical devices, air conditioners, refrigeration cabinets, measuring devices, etc. widely used in the fields. Application areas of thermoelectric modules and efforts to increase efficiency are in continuous development. In this study, an organ transport device with the thermoelectric cooling feature, which can be used in the medical field, was designed and performed and performance analyzes were made. An animal kidney measuring 5x6x10 cm was placed in the designed and realized system, and performance analyzes of the system were made at ambient temperatures of 25ºC, 30ºC, 35ºC, 40ºC. Each experiment was repeated five times and the average was taken. It was seen that the system, whose performance analyzes were carried out at different temperatures, was usable. The system’s small size, less weight and low cost compared to conventional cooling systems are among the important advantages of the system. It is possible to say that with the further development of the implemented system, larger organs can be cooled and transported and further studies can be carried out in this direction.